Corporate governance and the quality of accounting information - Zatta, Fernando Nascimento; Oliveira, Rodrigo Ribeiro de; Mattos, Aliomar Lino; Rocha, Alessandro Roberto; Gonçalves, Wellington; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2022)
Purpose - The aim of this study is to highlight the influence of corporate governance on the quality of accounting information in family businesses, specially the main governance mechanisms that influence the properties of the quality of accounting information. Design/methodology / approach - Based on data from 333 research articles, we adopted the bibliometric method in order to map the literature and also to disseminate scientific knowledge. Finding - The results obtained, supported by the literature, indicate that corporate governance mechanisms positively influence the quality of accounting information in family businesses. Originality / value - The selective and relevant literature provided sources of information for the study authors to discuss the growing importance of family businesses and the role of corporate governance and the quality of accounting information worldwide. The study includes the main authors who contributed to the development of an important topic related to the complexity of the family business, which constitutes a challenge for researchers and practitioners, reinforcing the originality of the present study.